2020
DOI: 10.1016/j.phrs.2020.105145
|View full text |Cite
|
Sign up to set email alerts
|

The disruption of protein-protein interactions as a therapeutic strategy for prostate cancer

Abstract: Prostate cancer (PCa) is one of the most common male-specific cancers worldwide, with high morbidity and mortality rates associated with advanced disease stages. The current treatment options of PCa are prostatectomy, hormonal therapy, chemotherapy or radiotherapy, the selection of which is usually dependent upon the stage of the disease. The development of PCa to a castration-resistant phenotype (CRPC) is associated with a more severe prognosis requiring the development of a new and effective therapy. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 184 publications
(272 reference statements)
0
13
0
Order By: Relevance
“…The prognosis for endocrine-independent prostate carcinoma (PC) is still poor due to its insensitivity to androgen deprivation therapy (ADT) or its highly metastatic feature (1). Therefore, it is valuable to explore the detailed mechanisms of resistance and progression in endocrine-independent PC cells, with specific focus on the molecular alterations that participate in the activation of androgen receptor (AR)-independent pathways (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for endocrine-independent prostate carcinoma (PC) is still poor due to its insensitivity to androgen deprivation therapy (ADT) or its highly metastatic feature (1). Therefore, it is valuable to explore the detailed mechanisms of resistance and progression in endocrine-independent PC cells, with specific focus on the molecular alterations that participate in the activation of androgen receptor (AR)-independent pathways (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Through NanoBRET ™ -based deletion mapping, we could pinpoint the first PHD domain of PHF6 as critical interface for the physical interaction with RRM2. Protein-protein interactions are increasingly recognized as an emerging drug modality and therefore we propose that pharmacological targeting PHF6-RRM2 is a promising therapeutic approach in cancer 62 . Given that we previously identified RRM2 as key replicative stress resistor in the context of neuroblastoma 26 , we aimed in this study to functionally evaluate the role of PHF6 in this tumor entity.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen related receptor alpha (ERRα) is involved in the regulation of prostate energy homeostasis ( 11 ). It has been shown that ERRα can interact with hypoxia inducible factor 1 (HIF) transcription factor complex to prevent HIF-1α from undergoing proteasomal degradation and augments the cellular adaptive response to hypoxia generated by the prostate tumour cells ( 94 , 95 ). As a result, interference of this indispensable PPI is a lucrative approach to develop prostate cancer therapeutics.…”
Section: Exploiting Other Proteins In a Transcriptional Complexmentioning
confidence: 99%
“…As a result, interference of this indispensable PPI is a lucrative approach to develop prostate cancer therapeutics. XCT790 is an inverse agonist of ERRα ( 94 ). It was demonstrated that administration of XCT790 attenuated ERRα-HIF-1 interactions and reduced the expressions of HIF-1 ( 95 ).…”
Section: Exploiting Other Proteins In a Transcriptional Complexmentioning
confidence: 99%